Mavrodes on the Nature of Arguments and the Epistemology of Moral Arguments for the Existence of God - Mohammad Saeed Akbari Dehghan; Naeme Poormohammadi (پژوهشنامه فلسفه دین, 2018)
In the classical tradition of arguments for the existence of God, a number of moral arguments have been proposed. Parallel to these arguments, moral arguments against the existence of God emerged. Here a question presents itself: does the existence of moral arguments against God discredit the ones for God and make the belief of theists unjustified? Our claim is that we can propose a new notion of argumentation which shields theistic moral arguments existence against atheistic ones. In this research, we have listed eight atheistic moral arguments and modified them with respect to Mavrodes’s theory of the nature of arguments; thereby proving that the theist is able to defend his moral arguments and that his belief is still justified. We are of course aware of the fact that this revision of the nature of arguments indicates the justification of atheistic arguments in their own respective viewpoints.